People management in micro and small companies (Research, Society and Development, 2022)
Micro and small companies are increasingly present in the world economy and thus are assuming a significant role in the market, especially in the national context. Thus, for the growth of these companies to stand out against competitors, ensuring productivity and quality of services offered to end customers, it is essential that people management be the great guide in the development of the organization, thus ensuring its stability. Given the above, the main objective of this study is to describe the importance of People Management promoted by it, in organizational success. From this context, the Personal Department sector becomes more valued, since the importance of human capital to face the globalized market is observed. Considering this perception, this study aims to research what are the difficulties in micro and small companies in relation to people management, and what obstacles are experienced. For a better understanding of this theme, a qualitative bibliographic review was carried out, based on books, scientific articles and websites focused on the air. It is verified that with people development programs in organizations, the small company better understands the training needs of its employees and seeks training, becoming increasingly competitive.